Differences in Ionospheric O+ and H+ Outflow During Storms With and Without Sawtooth Oscillations - N. Nowrouzi; L. M. Kistler; K. Zhao; E. J. Lund; C. Mouikis; G. Payne; B. Klecker (Geophysical Research Letters, 2024)
Abstract Previous simulations have suggested that O+ outflow plays a role in driving the sawtooth oscillations. This study investigates the role of O+ by identifying the differences in ionospheric outflow between sawtooth and non‐sawtooth storms using 11 years of FAST/Time of flight Energy Angle Mass Spectrograph (TEAMS) ion composition data from 1996 through 2007 during storms driven by coronal mass ejections. We find that the storm's initial phase shows larger O+ outflow during non‐sawtooth storms, and the main and recovery phases revealed differences in the location of ionospheric outflow. On the pre‐midnight sector, a larger O+ outflow was observed during the main phase of sawtooth storms, while non‐sawtooth storms exhibited stronger O+ outflow during the recovery phase. On the dayside, the peak outflow shifts significantly toward dawn during sawtooth storms. This strong dawnside sector outflow during sawtooth storms warrants consideration.